Gas‐phase hydration of the lysozyme ion produced by infrared‐laser ablation of a droplet beam studied by photodissociation and fluorescence spectroscopy. (28th July 2020) - Asami, Hiroya; Kawauchi, Norishi; Kohno, Jun‐ya
Abstract: Biomolecules function in an aqueous environment. Elucidation of the hydration structures of biomolecules is hence important to understand their functions. Here, we investigated the hydration structure of lysozyme (Lys) in the gas phase by photodissociation and fluorescence spectroscopy in combination with droplet‐beam laser ablation mass spectrometry. We found that water molecules are held inside and on the surface of the Lys molecule, and the hydration structure around the tryptophan residue changes by photoexcitation. This study provides a novel method to observe the hydration structures of large biomolecules at the molecular level.